Minimal-Invasive Analytical Method and Data Fusion: an Alternative for Determination of Cu, K, Sr, and Zn in Cocoa Beans - Gamela, Raimundo Rafael; Pereira-Filho, Edenir Rodrigues; Pereira, Fabíola Manhas Verbi [UNESP] (Springer Nature, 2021)
In the present study, a minimal-invasive analytical method for determination of Cu, K, Sr, and Zn in cocoa beans was performed using energy X-ray fluorescence (EDXRF) and laser-induced breakdown spectroscopy (LIBS) combined with multivariate calibration. Partial least squares (PLS) chemometric technique was applied to modeling the data, and inductively coupled plasma optical emission spectrometry (ICP OES) technique was the reference method for the chemical elements concentration levels, after microwave acid mineralization. The figures of merit estimated for Cu, Sr, Zn, and K showed good performance, with acceptable trueness values (85–120%). Data fusion strategy between EDXRF and LIBS data was used to enhance the predictive capability of K. In addition, lower standard error of cross-validation (SECV) (872 mg kg−1) was obtained, showing better performance than those obtained by individual data.
Keywords: Chemometrics; Direct solid analysis; Food samples; Nutrients; Partial least squares; Spectroanalytical techniques